IgG4-related intracranial hypertrophic pachymeningitis with skull hyperostosis: a case report - Lin, Che-Kuang (BioMed Central, 2013)
BACKGROUND: Immunoglobulin G4 (IgG4)-related disease is a systemic syndrome, characterized by sclerosing lesions and usually associated with a raised serum IgG4 level; the pancreas, salivary glands, and lacrimal glands are typically affected. Recently, it has been suggested that IgG4-related sclerosing disease represents a subset of cases previously diagnosed as idiopathic hypertrophic pachymeningitis. This rare inflammatory disorder causes localized or diffused thickening of intracranial dura mater. Headache, cranial nerve palsy, and ataxia are the most common clinical manifestations. Herein, we report the clinical and histopathological features of a rare case of IgG4-related intracranial hypertrophic pachymeningitis involving cranial hyperostosis. CASE PRESENTATION: A 52-year-old man presented with refractory generalized tonic-clonic seizure. Magnetic resonance imaging revealed thickening of the meninges with enhancement near the superior sagittal sinus; skull bone defect was also noted. Extensive excision of affected skull bone and dura was performed, providing the diagnosis of IgG4-related pachymeningitis. After the surgery, the patient’s seizure stopped and he was smoothly tapered off antiepileptic medication. CONCLUSION: To our knowledge, this is the first reported case of IgG4-related pachymeningitis with concomitant skull hyperostosis.